Pemanfaatan Website sebagai Proses Kemas Ulang Informasi di Universitas Perintis Indonesia - Sintia Sintia; Dhilla Afriani; Miftahul Syahirah Azalia (Asosiasi Profesi Telekomunikasi Dan Informatika Indonesia, 2025)
The rapid development of technology has an impact on information packaging. Website is a media used in the information repackaging process to make information more accessible. Website as the main media in distributing and managing information from various sources depending on user needs. Therefore, the website can be an innovation in the library world. This research aims to reveal the strategy and how the use of the website as a digital media has an impact on the dissemination of information packaging. This research method using descriptive qualitative method is used to comprehensively explain the impact of using the website in the data repackaging process at Universitas Perintis Indonesia. The utilization of the website as a process of information packaging at Perintis University is expected to run well and can be utilized as well as possible, so that the information that has been packaged is not in vain presented. However, it can also make it easier to obtain information quickly and relevantly without fear of an information explosion.